Application of graphitic carbon nitride (g-C3N4) in solid polymer electrolytes: A mini review - Minghao Ye; Binbin Li; Keyu Zhang; Rui Yan; Longbin Dai; Shaoze Zhang; Yin Li; Junxian Hu; Bin Yang; Yaochun Yao (Electrochemistry Communications)
Commercial lithium-ion batteries (LIBs) predominantly rely on liquid electrolytes, which are prone to various safety risks, such as leakage and combustion. Solid-state batteries (SSBs), represented by solid polymer electrolytes (SPEs), offer a dual advantage of enhancing safety and increasing energy density for electrochemical energy storage devices. However, the inherent characteristics of SPEs, such as high crystallinity and restricted molecular chain mobility, result in low ionic conductivity at room temperature, further limiting their commercial applications. Introducing inorganic fillers has proven to be an effective strategy to improve the ionic conductivity of SPEs. Graphitic carbon nitride (g-C3N4) stands out with its graphene-like two-dimensional planar structure, exhibiting exceptional physical properties (tunable electronic structure and excellent mechanical performance) and chemical stability (resistance to acid, alkali, and organic solvents). These attributes make it a widely researched for enhancing the comprehensive performance of SPEs. This paper provides a detailed overview of the synthesis techniques for g-C3N4, focusing on its action mechanisms for improving ion transport within SPEs. It comprehensively summarizes the applications and performance optimization strategies of g-C3N4 in SPEs, while also discussing future perspectives and directions for advancing the role of g-C3N4 in enhancing the performance of SPEs.